A dynamic storage assignment change method considering psychological stress among multiple workers in the logistics warehouse - Kirika MATSUDA; Seiya ICHIKAWA; Aya ISHIGAKI; Hiroyuki NISHIYAMA (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2022)
In logistics warehouses, customer needs have diversified and product life cycles have shortened. Hence, it is necessary to deliver various types products to retailers in a short period of time while responding to fluctuating demand. It is important to increase the efficiency of the order picking in warehouses. When multiple workers pick simultaneously, psychological stress develops due to the presence of other workers. When other workers pick on the storage rack, it is not possible to work on the same storage rack, leading to psychological waiting stress until picking of other workers is completed. In order picking, it is important to consider not only the work time but also the stress of workers. However, no research considers the psychological stress in order picking. We used multi-agent simulation and proposed a storage assignment change plan under fluctuating demand considering work time and psychological stress. We determined the optimal pattern of storage assignment change that minimizes work time or psychological stress according to the fluctuating demand. Assignment of work areas based on the optimal pattern of storage assignment changes further reduced work time and stress. By determining the reduction of either work time or stress and selecting the pattern of storage assignment change and assignment of work areas, flexible and appropriate picking operations can be performed according to the daily situation.